The impact of online recommendations on tourists' decision-making during the COVID-19 pandemic - Dražen Marić; Ksenija Leković; Sanja Džever (Anali Ekonomskog fakulteta u Subotici, 2024)
Electronic word-of-mouth recommendation system (eWOM) has been present since the emergence of the Internet, and it was preceded by the long-term use of the traditional recommendation system (WOM). Interaction between consumers can result in a positive and/or negative impact on theirs further behaviour on the market. Tourism industry attaches particular importance to the analysis of decision-making, given that the intangible nature of services makes the entire process difficult for tourists. Therefore, the aim of the paper is to examine the impact of online recommendations on the behaviour of tourist consumers in the decision-making process during the period of the COVID-19 virus pandemic. The subject of the paper is electronic word-of-mouth recommendation system, with a special focus on tourism. During the mentioned pandemic, the consumers' lifestyle was altered enormously, while tourism was affected by restrictions and difficult business operations. Empirical research was conducted on the territory of the Republic of Serbia and it included a sample of 268 respondents with different socio-demographic characteristics. Theanalysis of the obtained data was performed using the statistical software platform IBM SPSS Statistics and the Pearson's Correlation test, after which hypotheses 1, 2, 3 and 4 were accepted.